2021
DOI: 10.1080/00472336.2021.1905865
|View full text |Cite
|
Sign up to set email alerts
|

Pretending to be States: The Use of Facebook by Armed Groups in Myanmar

Abstract: Which functions do social media fill for non-state armed groups in countries with internal armed conflict? Building on conflict data, interviews and media monitoring, we have reviewed the use of social media by Myanmar's nine most powerful armed groups. The first finding is that they act like states, using social media primarily to communicate with their constituents. Second, they also use social media as a tool of armed struggle, for command and control, intelligence, denunciation of traitors, and attacks aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Such infamy prompted a shift in corporate policy, including hiring Myanmar-speaking content moderators, bringing on national advisors, and building dedicated country and regional expertise in the Singapore office. In the shadow of scandal, the platform’s public, interactive, and mobile-friendly features became critical to a wide range of domestic activities, from state-building to cultural preservation to online shopping (The-Thitsar 2021 ; Frydenlund and Shunn Lei 2021 ; Tønnesson 2022 ). For small farmers like the ones I lived and worked with, cheap SIM cards meant new forms of exchange and connection; rural people harnessed Facebook for securing livelihoods, supporting community and mobilizing for land justice.…”
Section: Research Site and Methodologymentioning
confidence: 99%
“…Such infamy prompted a shift in corporate policy, including hiring Myanmar-speaking content moderators, bringing on national advisors, and building dedicated country and regional expertise in the Singapore office. In the shadow of scandal, the platform’s public, interactive, and mobile-friendly features became critical to a wide range of domestic activities, from state-building to cultural preservation to online shopping (The-Thitsar 2021 ; Frydenlund and Shunn Lei 2021 ; Tønnesson 2022 ). For small farmers like the ones I lived and worked with, cheap SIM cards meant new forms of exchange and connection; rural people harnessed Facebook for securing livelihoods, supporting community and mobilizing for land justice.…”
Section: Research Site and Methodologymentioning
confidence: 99%
“…Furthermore, social media platforms can provide government agencies and decision-makers with the most up-to-date citizen sentiment regarding a developing crisis and assist them in creating a proper response and acting accordingly (Dong et al, 2021;Tagliacozzo, 2018;Zhou et al, 2018). This practice is especially relevant in natural disasters such as floods (Rossi et al, 2018), hurricanes (Yang & Stewart, 2019) or earthquakes when there is a combined need for preparedness, rescue and relief efforts (L. Li et al, 2018;Pourebrahim et al, 2019;Scott & Errett, 2018;Taylor et al, 2023). Previous studies have demonstrated that even though news outlets play a key role in the diffusion of information regarding these types of crises online (Kim et al, 2018), government agencies still have the ability to control the narrative and the messages disseminated to citizens to raise awareness towards them (Branicki & Agyei, 2015;Criado et al, 2020).…”
Section: Local Government In Times Of Crises and Emergenciesmentioning
confidence: 99%
“…Although many studies have focused on specific terrorist incidents, as in the aforementioned two examples, the research mostly overlook extensive events of military operations and armed conflicts and the role of local government bodies in social media. Thus, most of the relevant literature deals with national governments' efforts to advocate and represent their side of the conflict to different crowds and countries (Bahar, 2020; Manor & Crilley, 2018; Tønnesson et al, 2022). This is also the case for the ongoing armed conflict between Israel and the armed forces in Gaza, mostly Hamas and the Islamic Jihad.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another setting, mobile phones helped the Libyan Rebels avoid communication surveillance and obstruction dur-ing their fight against Gaddafi (Hill, 2011). Other examples include the use of Facebook and satellite phones by the Arakan Army rebel group in 2018-2020 in their fight against the National Army of Myanmar and the use of social media platforms by Al-Shabaab, Boko Haram, and ISIS to radicalize and recruit followers, coordinate activities, and secure funding (Cox et al, 2018;Tønnesson et al, 2021).…”
Section: Communications Technologymentioning
confidence: 99%